Conscientious Objection in Health Care: Pinning down the Reasonability View. Issue 1 (29th December 2020) - McConnell, Doug
Abstract: Robert Card's "Reasonability View" is a significant contribution to the debate over the place of conscientious objection in health care. In his view, conscientious objections can only be accommodated if the grounds for the objection meet a reasonability standard. I identify inconsistencies in Card's description of the reasonability standard and argue that each version he specifies is unsatisfactory. The criteria for reasonability that Card sets out most frequently have no clear underpinning principle and are too permissive of immoral objections. Card has also claimed that petitioners must justify their positions with Rawlsian public reason. I argue that, although the resulting reasonability standard is principled, it is overly restrictive. I also show that a reasonability standard built on Rawls' more lenient conception of reasonableness would be overly permissive of objections at odds with professional healthcare standards. Finally, I argue for my favored solution, which bases the reasonability standard on minimal professional standards.